"SYNTHESIS OF COPPER NANOPARTICLES BY TWO DIFFERENT METHODS AND SIZE COMPARISION" - UMESH KATHAD,; DR. H P GAJERA,; DR. H P GAJERA, (International Journal of Pharma and Bio Sciences, 2014)
The study was to determine the synthesis of copper nanoparticle by green chemistry and biological synthesis. In both method copper source remain same i.e. Copper Sulphate. Synthesis of the copper nanoparticles by green chemistry takes normal time in synthesis by using reducing agent ascorbic acid and size controlling by CTAB. The synthesis of copper nanoparticles by biological method was done using the plant (Artabotrys odoratissimus). It belongs to Annonaceae family. The local name is “Nag champo”. Size comparision of particles synthesized via two different techniques were done by Particle Size Analyser (PSA). Which indicate that between both method synthesis by Green Chemistry method gives average size particles of 35nm. While in case of Biological, it gives 135nm.